Treatment outcome with orthodontic aligners and fixed appliances: a systematic review with meta-analyses. (23rd November 2019) - Papageorgiou, Spyridon N; Koletsi, Despina; Iliadi, Anna; Peltomaki, Timo; Eliades, Theodore
Summary: Background: The use of orthodontic aligners to treat a variety of malocclusions has seen considerable increase in the last years, yet evidence about their efficacy and adverse effects relative to conventional fixed orthodontic appliances remains unclear. Objective: This systematic review assesses the efficacy of aligners and fixed appliances for comprehensive orthodontic treatment. Search methods: Eight databases were searched without limitations in April 2019. Selection criteria: Randomized or matched non-randomized studies. Data collection and analysis: Study selection, data extraction, and risk of bias assessment was done independently in triplicate. Random-effects meta-analyses of mean differences (MDs) or relative risks (RRs) with their 95% confidence intervals (CIs) were conducted, followed by sensitivity analyses, and the GRADE analysis of the evidence quality. Results: A total of 11 studies (4 randomized/7 non-randomized) were included comparing aligners with braces (887 patients; mean age 28.0 years; 33% male). Moderate quality evidence indicated that treatment with orthodontic aligners is associated with worse occlusal outcome with the American Board of Orthodontics Objective Grading System (3 studies; MD = 9.9; 95% CI = 3.6–16.2) and more patients with unacceptable results (3 studies; RR = 1.6; 95% CI = 1.2–2.0). No significant differences were seen for treatment duration. The main limitations of existing evidence pertained to risk of bias, inconsistency, and imprecision of included studies. Conclusions: Orthodontic treatment with aligners is associated with worse treatment outcome compared to fixed appliances in adult patients. Current evidence does not support the clinical use of aligners as a treatment modality that is equally effective to the gold standard of braces. Registration: PROSPERO (CRD42019131589).